The Implementation of Snake and Ladder Game in Teaching Speaking: The Advantages and The Disadvantages - Hayuningtyas, Nina (Critical Review of English-Arabic World Journal, 2022)
Speaking is one of the critical communication skills that students should be able to acquire. By speaking, they can convey thoughts, feelings, arguments, and ideas as well as emotions and other mental states. Yet, there are many problems faced by students in learning speaking. Due to those problems, choosing an appropriate media for teaching learning is an ability that every teacher must have. One of the entertaining and intriguing games that may be used to teach speaking is snake and ladder game. This study reports the advantages and the disadvantages of snake and ladder game in teaching speaking. While, the outcome can be summed up as follows: The Snake and Ladder game's design has both advantages and disadvantages. The advantages of the Snake and Ladder game is that it encourages students to practice speaking since it creates an enjoyable and relaxed learning environment. By forcing students to practice speaking since they must do so while playing, the snake and ladder game may help students indirectly enhance their English-speaking abilities. One of the drawbacks of the Snake and Ladder game is that it takes a lot of planning and practice time.